Analisis Kesulitan Menulis Paragraf Argumentasi Peserta Didik Fase B di Sekolah Dasar - Fitria Wilda; Chandra Chandra; Inggria Kharisma (Lencana: Jurnal Inovasi Ilmu Pendidikan, 2025)
This study aims to analyze the difficulties faced by Phase B Elementary School students inwriting argumentative paragraphs. The ability to write argumentative paragraphs is an important skill in language learning, because it involves the ability to think critically, organize ideas logically, and express opinions with supporting reasons. However, students at this age often have difficulty in formulating clear arguments, organizing ideas, and using effective language. This study uses a qualitative descriptive method with data collection techniques through observation, interviews, and analysis of student-written documents. The results of the study indicate that the main challenges faced by students include: difficulty in choosing a title that is appropriate to the topic, lack of skills in organizing ideas systematically, limited vocabulary and grammar mastery, and low motivation to write due to lack of reading and writing habits. This study emphasizes the need for more innovative learning strategies, such as a scientific approach and the importance of teachers providing intensive training in developing vocabulary, sentence structure, and logical thinking so that students can write argumentative paragraphs better.